Identifikasi Tumbuhan Obat dan Pemanfaatannya oleh Battra di Desa Doulu Kabupaten Karo - Roy Franata Tarigan; Fathul Yusro; Yanieta Arbiastutie; Yeni Mariani (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Battra is a person who can blend various plants into medicines used in traditional medicine processes. This study aims to identify and analyze the medicinal plants used by Battra in Doulu Village, Karo Regency, North Sumatra Province. This study uses a survey method with a tool in the form of an interview guide. Interviews with battra were conducted in-depth to find out information about the medicinal plants they use, what parts of the plants are used, and their processing techniques and uses. The study results show that Battra in Doulu Village, Karo Regency, is still practicing traditional medicine. Battra in this village utilizes 31 types of medicinal plants. The highest plant family used was Zingiberaceae. The most utilization by battra was in herbaceous habitus, which was 39%, plant parts in the form of leaves (35%), the processing carried out by chopping (39%), and the use of medicinal plants by eating (48%).